2016
DOI: 10.1007/s10495-016-1310-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of apoptotic cell clearance by macrophage nuclear receptors

Abstract: Apoptotic cell clearance by macrophages is key for normal tissue development and homeostasis. Nuclear receptors, such as peroxisome proliferator activated receptors (PPARs), liver X receptor (LXR), retinoic acid receptor (RAR), retinoid X receptor (RXR) and glucocorticoid receptor (GR) orchestrate this vital process. The underlying mechanism involves the transcriptional control of key genes of apoptotic cell recognition and internalization, such as Cd36, Mertk, Axl, C1qa, Tgm2, Abca1. In addition, apoptotic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 72 publications
2
58
0
1
Order By: Relevance
“…The cluster analysis (Table S2) indicates that there are only few transcripts that share a transcription pattern with MARCO, of which only VSIG4 and GPR34 were highly-expressed. The underlying transcriptional regulation is also consistent with data from mice, in that genes encoding known regulators of apoptotic receptors in mice, NR1H33 and PPARG (51) were also strongly-enriched in the chicken Kupffer cells. In mice, Kupffer cells are required for the elimination of senescent red blood cells and recycling of iron (52).…”
Section: Discussionsupporting
confidence: 87%
“…The cluster analysis (Table S2) indicates that there are only few transcripts that share a transcription pattern with MARCO, of which only VSIG4 and GPR34 were highly-expressed. The underlying transcriptional regulation is also consistent with data from mice, in that genes encoding known regulators of apoptotic receptors in mice, NR1H33 and PPARG (51) were also strongly-enriched in the chicken Kupffer cells. In mice, Kupffer cells are required for the elimination of senescent red blood cells and recycling of iron (52).…”
Section: Discussionsupporting
confidence: 87%
“…Different studies have shown that PPAR and LXR are activated in macrophages in response to apoptotic cells and express genes such as the cholesterol transporter ABCA1 and phospholipid transporter, phospholipid transfer protein 1 (PLTP1). Moreover, PPAR and LXR activity upregulate the expression of phagocytic receptors (Mer, CD36 and Axl) and opsonins (C1qb, Gas6, MFG-E8,) that support phagocytic activity and continuous engulfment of apoptotic bodies [118, 119]. Perhaps the most interesting feature of PPAR and LXR activation in response to efferocytosis that points towards a putative role in macrophage function is the induction of anti-inflammatory IL-10, and prevention of inflammatory cytokine production [120122].…”
Section: Implications Of Lap In Macrophage Immunometabolismmentioning
confidence: 99%
“…In addition, the αvβ3 integrin express on phagocytes can bind to thrombospondin, helping the recognition of PS on the surface of apoptotic cells (51). Other apoptotic cell recognition receptors, such as the family of receptor tyrosine kinases Tyro3, Axl, and MerTK (TAM), also need to bind to bridge molecule to interact with PtdSer on the surface of apoptotic cells (5254). …”
Section: Apoptosis As a Hallmark Of T Cruzi Infectionmentioning
confidence: 99%